2018
DOI: 10.1002/ijc.31548
|View full text |Cite
|
Sign up to set email alerts
|

Mutant MYO1F alters the mitochondrial network and induces tumor proliferation in thyroid cancer

Abstract: Familial aggregation is a significant risk factor for the development of thyroid cancer and familial non-medullary thyroid cancer (FNMTC) accounts for 5-7% of all NMTC. Whole exome sequencing analysis in the family affected by FNMTC with oncocytic features where our group previously identified a predisposing locus on chromosome 19p13.2, revealed a novel heterozygous mutation (c.400G > A, NM_012335; p.Gly134Ser) in exon 5 of MYO1F, mapping to the linkage locus. In the thyroid FRTL-5 cell model stably expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…A recent study has shown that mutated MYO1F alters the mitochondrial network and induces tumor proliferation in thyroid cancer [67]. This arises due to a mutated MYO1F gene at the TCO locus (Gly134Ser) that leads to increased oncogenic potential in vitro in terms of cell growth and invasion.…”
Section: Myo1fmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that mutated MYO1F alters the mitochondrial network and induces tumor proliferation in thyroid cancer [67]. This arises due to a mutated MYO1F gene at the TCO locus (Gly134Ser) that leads to increased oncogenic potential in vitro in terms of cell growth and invasion.…”
Section: Myo1fmentioning
confidence: 99%
“…However, in the mutant cell lines, analysis by live-cell visualization revealed that the mitochondria appeared as separate rod-shaped organelles with increased mass that produced significantly more intracellular and extracellular reactive oxygen species. How MYO1F regulates the mitochondrial network needs to be addressed.Several somatic mutations in MYO1F related to different types of cancer have been found in genetic databases [67]. One example is the fusing of the mixed lineage leukemia gene with the MYO1F gene, which has been described as recurrent in infant acute monocytic leukemia [68,69].…”
Section: Myo1fmentioning
confidence: 99%
“…It has been demonstrated that the overall heritability of thyroid cancer is high compared with other cancers 4–7. Classic linkage studies in familial papillary thyroid cancer have revealed a small number of culpable loci; however, heritable germline pathogenic variants have been largely absent from familial and sporadic cases 8–19. Therefore, we hypothesised that the genetic risk predisposing to thyroid cancer is due to complex genetic factors and a combination of low penetrance alleles.…”
Section: Introductionmentioning
confidence: 98%
“…In general, TC has few obvious symptoms and is usually found by neck examination. Such cancer has a tendency of family aggregation, but its genetic basis is not totally clear [4] . At present, TC is mainly divided into four categories, namely papillary thyroid cancer (PTC), follicular thyroid cancer (FTC), medullary thyroid cancer (MTC) and anaplastic thyroid cancer (ATC).…”
Section: Introductionmentioning
confidence: 99%